Preparation and Identification of some heterocyclic compounds from cyano compounds - Ibtehal K. Abdullah; Meaad K. Buniya (Tikrit Journal of Pure Science, 2023)
This article included prepared cyano acetic acid hydrazid from interaction cyano ethylacetate with hydrate hydrazen, and interaction with 2- acytel thiophene and 2- acytelpyridine it will formation of hydrazide- hydrazone derivative (I, II), and through the undergo the compounds (I,II) for chain of interactions with different chemical materials then enclosed cyclo formed derivative of  (arylidene ,coumarin , aryl hydrazon , thiophene ) .